PENGARUH UKURAN PERUSAHAAN, LEVERAGE, KUALITAS AUDIT DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG (PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON-PRIMER SUBSEKTOR PERDAGANGAN RITEL - Pratiwi, Nelysa Farayoga Sriya; Suwarno, Agus Endro (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the effect of company size, leverage, audit quality and audit opinion on audit report lag in non-primary consumer goods sector companies in the retail trade subsector listed on the Indonesia Stock Exchange in 2019-2022. This research uses quantitative data. The sampling technique was carried out by purposive sampling method, which resulted in 51 samples. The tests carried out in this study were multiple linear regression tests with the SPSS test tool. The results of this study indicate that simultaneously company size, leverage, audit quality and audit opinion have no effect on audit report lag. Partially, the audit quality variable has an effect on audit report lag. Meanwhile, company size, leverage and audit opinion have no effect on audit report lag